ALTERNATIVE STUDY ON PROCESSING OIL PALM EMPTY FRUIT BUNCHES AS SUITABLE FUEL AND COMPLYING WITH STANDARDS FOR POWER PLANTS - Doni, Dionisius Doni; Junaidi, Junaidi; Danial, Danial (Faculty of Engineering, Universitas Tanjungpura, 2023)
Indonesia possesses a substantial potential in renewable energy resources, one of which emanates from waste. Palm oil waste biomass stands as a viable energy source, aligned with the escalating adoption of renewable energy in the country, as outlined in the national 2025 primary energy mix targets, which emphasize augmenting biomass utilization as an energy source. The artificial drying process of oil palm empty fruit bunches utilizing an electric drying apparatus at a temperature of 150°C, for durations of 10 and 20 minutes, is geared towards achieving low moisture content and enhanced calorific value of dried empty fruit bunches, rendering them efficient for employment as feedstock in Power Plants. Based on the findings of the 10-minute drying study, a moisture content of 7.88% was attained, in adherence to the Indonesian National Standard (SNI) 01-6235-2000 stipulating 8%. Additionally, the calorific value registered at 4353 kcal/kg. The constructed drying mechanism yielded electricity costs of Rp. 563,433 for a 10-minute drying session each 1 kg sample and Rp. 924,636894 for a 20-minute drying cycle each identical sample weight.